2011
DOI: 10.1161/circinterventions.110.959718
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Percutaneous Transluminal Septal Myocardial Ablation in Hypertrophic Obstructive Cardiomyopathy

Abstract: In this multicenter study, the in-hospital mortality after PTSMA was low despite considerable comorbidities. The hemodynamic and symptomatic effects were sustained long term. The long-term symptomatic outcome was associated with baseline comorbidities. The 10-year survival rate was comparable to that in an age- and sex-matched background population, and age was the only predictor of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 34 publications
5
52
1
7
Order By: Relevance
“…And, as survival after myectomy, survival after ASA is also comparable with that of general population [8,9]. These data support the notion that ASA may be another intervention which improves survival of patients with obstructive HCM and severe drug-refractory symptoms.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…And, as survival after myectomy, survival after ASA is also comparable with that of general population [8,9]. These data support the notion that ASA may be another intervention which improves survival of patients with obstructive HCM and severe drug-refractory symptoms.…”
Section: Introductionsupporting
confidence: 75%
“…However, we are still not sure whether this technique extends longevity of its target patients. Results from several studies suggest that ASA can extend longevity of patients with HCM [6][7][8][9][10][11][12]. Here, we extended evidence for this notion by directly comparing the survival of patients undergoing ASA vs. a group of conservatively treated patients with comparable pressure gradient and limiting symptoms.…”
Section: Discussionmentioning
confidence: 64%
“…114 Finally, a Scandinavian study reported marked reductions in outflow tract gradients in response to 313 ablation procedures in 279 patients with HCM, of whom 94% had class III/IV symptoms. 115 Only 21% had class II/IV symptoms at 1 year, with little change thereafter. Estimated survival rates at 1, 5 and 10 years were 97%, 87% and 67%, respectively, and were comparable to survival rates in an age-and gendermatched population.…”
Section: Alcohol Septal Ablation In Hypertrophic Cardiomyopathymentioning
confidence: 98%
“…Among the inva sive group, the pacemaker-treated group fared less well than patients treated with septal ablation or myomectomy, ques tioning the call for a reappraisal of pacemaker therapy in a recent Spanish study that reported favourable long-term results in a group of 50 patients. 114 Finally, a Scandinavian study reported marked reductions in outflow tract gradients in response to 313 ablation procedures in 279 patients with HCM, of whom 94% had class III/IV symptoms. 115 Only 21% had class II/ IV symp toms at 1 year, with little change thereafter.…”
Section: Alcohol Septal Ablation In Hypertrophic Cardiomyopathymentioning
confidence: 98%